Community engagement and involvement in managing the COVID-19 pandemic among urban poor in low-and middle-income countries: a systematic scoping review and stakeholders mapping. Issue 1 (31st December 2023) - Sahoo, Krushna Chandra; Sahay, Mili Roopchand; Dubey, Shubhankar; Nayak, Subhasish; Negi, Sapna; Mahapatra, Pranab; Bhattacharya, Debdutta; Barrio, Mariam Otmani Del; Pati, Sanghamitra
ABSTRACT: Background: Community engagement and involvement (CEI) was crucial for the COVID-19 pandemic response, particularly among the urban poor in low-and middle-income countries (LMICs). However, no evidence synthesis explores how CEI can benefit public health emergencies. Objective: We conducted a systematic scoping review of the CEI with an emphasis on stakeholder identification, accountability mapping, the support system, and the engagement process among urban poor populations in LMICs during the COVID-19 pandemic. Methods: We searched eleven databases, including PubMed, Embase, Web of Science, and CINAHL, following the PRISMA-2020 guidelines to find articles published between November 2019 and August 2021. PROSPERO registration No: CRD42021283599. We performed the quality assessment using a mixed-method appraisal tool. We synthesized the findings using thematic framework analysis. Results: We identified 6490 records. After the title and abstract screening, 133 studies were selected for full-text review, and finally, we included 30 articles. Many stakeholders were involved in COVID-19 support, particularly for health care, livelihoods, and WASH infrastructure, and their accountability mapping by adopting an interest – influence matrix. This review emphasizes the significance of meaningful CEI in designing and implementing public health efforts for pandemic management among urban slum populations. The interest – influence matrix findings revealed that specific community volunteers, community-based organizations, and civil society organizations had high interest but less influence, indicating that it is necessary to recognize and engage them. Conclusion: Motivation is crucial for those with high influence but less interest, such as corporate responsibility/conscience and private food supply agencies, for the health system's preparedness plan among urban populations.